2007
DOI: 10.1051/parasite/2007142135
|View full text |Cite
|
Sign up to set email alerts
|

Blood schizontocidal activity of methylene blue in combination with antimalarials againstPlasmodium falciparum

Abstract: Summary :Methylene blue (MB) is the oldest synthetic antimalarial. It is not used anymore as antimalarial but should be reconsidered. For this purpose we have measured its impact on both chloroquine sensitive and resistant Plasmodium strains. We showed that around 5 nM of MB were able to inhibit 50 % of the parasite growth in vitro and that late rings and early trophozoites were the most sensitive stages; while early rings, late trophozoites and schizonts were less sensitive. Drug interaction study following f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 30 publications
(34 reference statements)
5
21
0
Order By: Relevance
“…Our ex vivo study presents additional evidence for NQ's potent activities against highly CQ-resistant isolates of P. falciparum and P. vivax, revealing lower IC 50 s for NQ than for all of the standard drugs with the exception of AS. The ex vivo activity of MB was greater than that of NQ, in line with previous observations in P. falciparum (19)(20)(21)(22)(23)(24)39) and P. vivax (30), with lower IC 50 s than those for all standard drugs, including AS, for both species.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our ex vivo study presents additional evidence for NQ's potent activities against highly CQ-resistant isolates of P. falciparum and P. vivax, revealing lower IC 50 s for NQ than for all of the standard drugs with the exception of AS. The ex vivo activity of MB was greater than that of NQ, in line with previous observations in P. falciparum (19)(20)(21)(22)(23)(24)39) and P. vivax (30), with lower IC 50 s than those for all standard drugs, including AS, for both species.…”
Section: Discussionsupporting
confidence: 77%
“…The current study also confirms MB's remarkable ex vivo efficacy against resistant strains of P. falciparum and P. vivax, showing high potency, a broad stage specificity of action, including gametocyte stages (25), and synergism with other antimalarials (19,21,44). Although researchers and drug developers have been aware of the antimalarial properties of MB against P. falciparum for almost a century, it has never been widely used in clinical practice, largely due to its poor tolerability profile.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…This quassinoid, named simalikalactone E, exhibited very good antiplasmodial activity against the three P. falciparum strains tested, whatever their geographic origin or chloroquine sensitivity. The IC 50 s obtained were in the range of most commercially available antimalarial drugs tested under similar conditions (16) Against P. falciparum gametocytes, a stage which is fundamental for transmission to mosquitoes, SkE was more active (IC 50 , 1.2 M) than the reference compound primaquine (IC 50 , 8.9 M). In a previous study, Benoit-Vical et al (3) showed that an artemisinin derivative, artesunate, inhibited gametocyte growth at a 10-fold-lower dose (around 0.1 M).…”
Section: Biodiversity Is Clearly a Source Of New Drugs (26) When Biomentioning
confidence: 73%
“…The safety and gametocytocidal activity of alternative drugs from the same family as PQ (the 8-aminoquinolines), such as bulaquine (CDRI 80/53) (162, 163) and tafenoquine (WR-238605) (99,100,371,487), require further investigation. Methylene blue, which together with quinine served as a structural starting point for the development of 8-aminoquinolines (153,406), was recently suggested as an alternative safe gametocytocidal component of drug combinations (103,531) and may be a promising gametocytocidal component of combination therapy.…”
Section: Effects Of Drugs On Gametocytemiamentioning
confidence: 99%